Evaluation of the Implementation of Pharmaceutical Service Standards at the Toto Kabila Regional General Hospital, Bone Bolango Regency - Rahmawanto Taidi; Yosep P. Koton; Laksmyn Kadir (Universitas Muhammadiyah Palu, 2023)
Objective: To evaluate and analyze the inhibiting factors in the implementation of pharmaceutical service standards (including human resources, administration, facilities and infrastructure) related to the management of pharmaceutical supplies and clinical pharmacy services at RSUD Toto Kabila. Research method: using descriptive qualitative research using data collection techniques through observation, interviews and documentation and using data analysis techniques in data reduction, data presentation and conclusion drawing. Research results: 1) Evaluation of the implementation of pharmaceutical service standards at the Toto Kabila Hospital Pharmacy Installation in terms of effectiveness, efficiency and accuracy has followed the rules issued by the Permenkes but the results have not been maximized; 2) There are 3 supports in carrying out the implementation of pharmaceutical standards, namely, human resources, administration, facilities and infrastructure.